2019
DOI: 10.2340/16501977-2498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term use of ankle-foot orthoses on tibialis anterior muscle electromyography in patients with sub-acute stroke: A randomized controlled trial

Abstract: LAY ABSTRACTAnkle-foot orthoses (AFOs) are often used to improve walking after stroke. However, it is unknown whether early or later provision of AFOs affects muscle activity, and what are the effects of long-term AFO use after stroke. Some clinicians fear that early use of AFO after stroke has negative effects on muscles around the ankle. Therefore, we studied the effect of AFO use on the tibialis anterior muscle in 26 subjects after stroke. Subjects were prescribed an AFO in week 1 of the study, or 8 weeks l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…Nikamp et al reported that at an average of 30 days after stroke onset, TA muscle activity decreased more during swing when using a PAFO than when not using a PAFO, but there was no significant difference in muscle activity with or without a PAFO after 26 weeks. 5 ) However, we found that in patients with stroke, 2-month use of an AFO-PR that allows plantarflexion of the ankle joint during loading response resulted in significant increases in TA %EMG activity during loading response compared with the other phases.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Nikamp et al reported that at an average of 30 days after stroke onset, TA muscle activity decreased more during swing when using a PAFO than when not using a PAFO, but there was no significant difference in muscle activity with or without a PAFO after 26 weeks. 5 ) However, we found that in patients with stroke, 2-month use of an AFO-PR that allows plantarflexion of the ankle joint during loading response resulted in significant increases in TA %EMG activity during loading response compared with the other phases.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast, Nikamp et al reported that at an average of 30 days after stroke onset, TA muscle activity decreased more during swing when using a PAFO than when not using a PAFO, but there was no significant difference in muscle activity with or without a PAFO after 26 weeks. 5) The AFO-PS and PAFO used in these previous studies may have affected TA muscle activity by stopping plantarflexion during loading response. Recently, AFOs with plantarflexion resistance (AFO-PR) have been developed to aid the eccentric contraction of the TA muscle in the heel rocker.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…67 These beneficial effects on functional outcomes were found without negative consequences of AFO-use on muscle activity of the tibialis anterior. 106 In addition, decreased foot-clearance is reported as an increased risk for stumbling and falls. 11 AFOs are provided to improve foot-clearance in swing phase, 14 under the assumption that this improves safety of walking.…”
Section: Discussionmentioning
confidence: 99%
“…were studied and several outcome levels were used. The effects of timing of providing AFOs on clinical scales, 65,83 lower limb kinematics 82,92 and tibialis anterior muscle electromyography 106 have been previously reported. In the current paper, the early group (provided with AFOs after inclusion), was compared with the delayed group (not yet provided with AFOs)…”
Section: Introductionmentioning
confidence: 93%